Influence of six years of no-tillage and conventional plowing on fertilizer response of maize (Zea mays L.) on an alfisol in the tropics - Lal, R. (1979)
The effects of four rates of N (0, 40, 80, and 120 kg/ha) and three rates of P (0, 13, and 26 kg/ha) on maize (Zea mays L.) response were investigated for no‐tillage and conventionally plowed plots on an Alfisol in southwestern Nigeria. These, experiments were conducted for three consecutive seasons. Notillage treatments yielded more than conventionally plowed plots in all three seasons. The mean yields were 2.90 and 2.42 metric tons/ha, respectively. There was no effect of P on grain yield. Nitrogen application had a significant effect on grain yield in all three seasons. Relative grain yield in the plowed plots without N application was 0.85 of that in no‐tillage plots. These results, obtained 6 years after adopting these tillage systems, are contradictory to those obtained in the first year of adopting these tillage practices. Leaf concentration of N was affected only by levels of N application.